To the 90th anniversary of the birth of A. I. Kokorin. Stages of scientific and pedagogical way - V. V. Bludov; N.A. Peryazev; S.F. Vinokurov; V.I. Panteleyev (Известия Иркутского государственного университета: Серия "Математика", 2019)
The paper is devoted to the scientific and pedagogical activity of A. I. Kokorin, the founder of the Irkutsk algebraic-logical school, whose 90th anniversary is celebrated in November 2019. Five research areas with the most significant contributions made by A. I. Kokorin are described. A brief overview of his achievements in each area is established. A list of publications, as well as that of dissertations, defended under supervising by A. I. Kokorin is given.